FRI0113 A study of a cohort of lupus patients with acute gastrointestinal manifestations of active disease. (1st June 2001) - Lian, TY; Edwards, CJ; Chng, HH
Abstract : Background: Gastrointestinal symptoms occur commonly in SLE, but vasculitis of the bowel or SLE related gut disease (lupus gut) have previously been described to be of low incidence. These reports have usually been based on cases admitted with acute abdomen, associated with high mortality. Our experience in Singapore suggests that a milder form of this entity may manifest as acute gastrointestinal symptoms. Objectives: To study the clinical characteristics, management and outcome of SLE patients admitted with acute gastrointestinal symptoms and treated as lupus gut after exclusion of infection or other aetiology. Methods: The case notes of 20 SLE patients admitted for acute gastrointestinal symptoms and treated as lupus gut were reviewed. All patients satisfied the ACR criteria. We defined lupus gut as patients presenting with abdominal pain, vomiting and/or diarrhoea with raised double stranded DNA or hypocomplementemia and whose gastrointestinal symptoms responded to parenteral corticosteroids, increased oral corticosteroids or immunosuppressants. SLEDAI scores were also performed for disease activity. Results: All our patients were females and most were Chinese (95%). The mean age at presentation was 35.7 (13–56 years) and mean duration of SLE to their admission for lupus gut was 6.7 years (1–15 years). Most patients presented with abdominal pain (90%), diarrhoea (75%) and vomiting (70%). Abdominal tenderness was a frequent finding (70%) and 25% were febrile. Double stranded DNA was raised in all 17 patients who had this investigation performed and 75% had hypocomplementemia. Blood and stool cultures were carried out in 55% and 60% of patients respectively and all were negative. The mean SLEDAI score was 5.3 (0–12). Intravenous drip was commenced in 75% of patients with resting of gut and 80% received intravenous hydrocortisone. Intravenous methylprednisolone was administered to 5 patients (25%), 4 of whom had not responded to initial intravenous hydrocortisone. The majority (75%) had a good outcome with resolution of their abdominal symptoms, discharged well from hospital including 1 patient who underwent a laparotomy and was found to have patchy ischmic small bowel. Lupus gut recurred in 4 (20%) patients on subsequent follow up (mean follow up 31.4 months) and all 4 again responded to similar therapy. Three patients died within 4 months of their admission, 2 of whom had developed active nephrits 1 month prior to their death. Conclusion: Our study suggests that SLE related gut disease may occur in milder forms more commonly than previously described. Symptoms are associated with markers of active disease and respond to conventional treatment for SLE and resting of gut. References: Sultan SM, Ioannou Y, Isenberg DA. A review of gastrointestinal manifestations of systemic lupus erythematosus. Rheumatology 1999;38:917–32 Zizic TM, Classen JN, Stevens MB. Acute abdominal complications of systemic lupus erythematosus and polyarteritis nodosa. Am J Med. 1982;73:525–31 Medina F, Ayala A, Jara LJ, et al . Acute abdomen in systemic lupus erythematosus: the importance of early laparotomy. Am J Med. 1997;103:100–5